α‐tACS over the somatosensory cortex enhances tactile spatial discrimination in healthy subjects with low alpha activity - Saito, Kei; Otsuru, Naofumi; Yokota, Hirotake; Inukai, Yasuto; Miyaguchi, Shota; Kojima, Sho; Onishi, Hideaki (Brain and behavior, 2021)
Introduction Spontaneous oscillations in the somatosensory cortex, especially of the alpha (8 − 14 Hz) and gamma (60 − 80 Hz) frequencies, affect tactile perception; moreover, these oscillations can be selectively modulated by frequency‐matched transcranial alternating current stimulation (tACS) on the basis of ongoing oscillatory brain activity. To examine whether tACS can actually improve tactile perception via alpha and gamma modulation, we measured the effects of 10‐Hz and 70‐Hz tACS (α‐ and γ‐tACS) on the left somatosensory cortex on right‐finger tactile spatial orientation discrimination, and the associations between performance changes and individual alpha and gamma activities. Methods Fifteen neurologically healthy subjects were recruited into this study. Electroencephalography (EEG) was performed before the first day, to assess the normal alpha‐ and gamma‐activity levels. A grating orientation discrimination task was performed before and during 10‐Hz and 70‐Hz tACS. Results The 10‐Hz tACS protocol decreased the grating orientation discrimination threshold, primarily in subjects with low alpha event‐related synchronization (ERS). In contrast, the 70‐Hz tACS had no effect on the grating orientation discrimination threshold. Conclusions This study showed that 10‐Hz tACS can improve tactile orientation discrimination in subjects with low alpha activity. Alpha‐frequency tACS may help identify the contributions of these oscillations to other neurophysiological and pathological processes. 10‐Hz tACS can improve tactile orientation discrimination in subjects with low alpha activity. Conversely, 70‐Hz tACS had no effect on tactile orientation discrimination.